2015
DOI: 10.3343/alm.2015.35.6.595
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of β-Lactamase Genes Among Carbapenem-ResistantKlebsiella pneumoniaeStrains Isolated From Patients in Turkey

Abstract: BackgroundThe emergence of carbapenem-resistant Klebsiella pneumoniae poses a serious problem to antibiotic management. We investigated the β-lactamases in a group of carbapenem-resistant K. pneumoniae clinical isolates from Turkey.MethodsThirty-seven strains of K. pneumoniae isolated from various clinical specimens were analyzed by antimicrobial susceptibility testing, PCR for the detection of β-lactamase genes, DNA sequencing, and repetitive extragenic palindronic (REP)-PCR analysis.ResultsAll 37 isolates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
32
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 28 publications
5
32
1
3
Order By: Relevance
“…In the present study, KPC, IMP, and VIM were not determined from any of the isolates. Similar to the current study data, 2 recent studies performed on carbapenem-resistant K. pneumoniae clinical isolates from different hospitals of Turkey, no positive results for KPC, IMP, and VIM enzymes were reported (40,41). In a multicentral surveillance study, the prevalence of VIM, IMP, and KPC among 136 carbapenemresistant E. coli and K. pneumoniae isolates was reported as 2.8%, 1.4%, and 0%, respectively (33).…”
Section: Discussionsupporting
confidence: 74%
“…In the present study, KPC, IMP, and VIM were not determined from any of the isolates. Similar to the current study data, 2 recent studies performed on carbapenem-resistant K. pneumoniae clinical isolates from different hospitals of Turkey, no positive results for KPC, IMP, and VIM enzymes were reported (40,41). In a multicentral surveillance study, the prevalence of VIM, IMP, and KPC among 136 carbapenemresistant E. coli and K. pneumoniae isolates was reported as 2.8%, 1.4%, and 0%, respectively (33).…”
Section: Discussionsupporting
confidence: 74%
“…Udomsantisuk et al 53 reported that the frequency of the bla VEB gene was 30% among β-lactamase-positive K. pneumoniae strains; however, in the current study, the frequncy of bla VEB gene was 12%. Iraz et al 54 reported that 86% of the carbapenem-resistant K. pneumoniae strains carried the bla OXA gene; however, Charrouf et al 55 found that only 6% of their isolates carried this gene. Our results did not match either of these studies; in our study, the prevalence of this gene was 28%.…”
mentioning
confidence: 99%
“…Yunanistan'da 2007 yılında yapılan bir çalışmada, çoklu ilaç direnci bulunan patojenlerle enfeksiyon nedeniyle kolistin kullanılan yoğun bakım hastalarında, kolistine dirençli K. pneumoniae ile bronşiyal ve bağırsak kolonizasyon oranı %37 olarak saptanmıştır (20). Karbapenem dirençli K. pneumonia suşlarında da İtalya'da %43, Türkiye'de %2,7 kolistin direnci bildirilmiştir (21,22). Yine İtalya'dan bildirilen bir çalışmada, karbapenemaz üreten K. pneumonia suşlarında kolistin direncinin 2010-2013 yılları arasında %11'den %27'ye yükseldiği belirtilmiştir (23).…”
Section: Methodsunclassified